PENGECUALIAN LARANGAN ABORSI BAGI KORBAN PERKOSAAN SEBAGAI JAMINAN HAK-HAK REPRODUKSI - Putu Mas Ayu Cendana Wangi; Sagung Putri M.E. Purwani (Kertha Negara : Journal Ilmu Hukum, 2013)
Pregnancy due to rape is not only causes physical, mental and social suffering forthe victim, but also very opposed to her reproductive rights. The problem that arisesthen is when the victim decides to have an abortion. According to the Penal Code, anyform of abortion is a crime, but The Act Number 36 Year 2009 regarding The Healthdefine exceptions abortion ban with any requirements. Therefore, this paper will discussmore about an abortion for rape victim and its relation to reproductive rights.